Upaya Mempertahankan Bisnis Radio Siaran Di Era Kemajuan Teknologi Informasi (Studi Pada Empat Perusahaan Radio Siaran di Kabupaten Kebumen) - Hendrawan Prasetyo (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2019)
The problem in this study is about how the radio broadcast business in the era of technological advancements and information, whether radio broadcasts can still maintain their existence and are still in the public interest as an effective means of entertainment and information and what radio broadcast companies do in facing business challenges in the era technological progress and information so that it can survive. The method used in this study is a qualitative research method, taking data sources using a "purposive sampling" technique with a total of 4 (four) informants including the management of radio broadcast companies in 4 (four) radio broadcast companies in the researched Kebumen Regency. Data collection in this study was carried out through observation, documentation and in-depth interviews. Observations and interviews are used to capture primary data relating to how important radio broadcast companies view technological and information progress as challenges that must be faced to maintain the existence of broadcast radio. While the study of documentation is used to capture secondary data that can be raised from various documentation about media data, broadcast radio company profiles and so on. The data analysis technique in this study is an interactive model analysis, including four components, namely data collection, data reduction, data presentation and conclusions or verification. The theory used is the theory of general communication and business communication. The locus of research in four radio broadcast companies in Kebumen District, namely: Bimasakti FM Kebumen, Mas FM Kebumen, RPFM Gombong, and Radio Gong FM Gombong, the results of this study found that advances in technology and information will raise efforts to improve the quality of broadcast radio companies in Kebumen through various ways including the ability to adjust to follow the advances in technology and information carried out by changing the conventional ways of broadcasting in a more modern way with technology-based and internet-based information. The four radio broadcast companies in Kebumen Regency were examined, although in general they had adjusted to the advancement of technology and information in order to maintain their existence. In fact there were still a number of radio broadcast companies that had not implemented streaming broadcasts so that the range that could be received by audiences or listeners was limited and not yet global. Efforts to adjust to the advancement of technology and information must, of course, be accompanied by efforts to improve the quality of human resources broadcast radio companies both internally and externally. Keywords: business communication, existence, radio broadcast, streaming, technological progress.